Soviet Historiography of the USSR-FRG Energy Cooperation between the 1960s and 1980s - Elena Anatolyevna Igisheva; Sophia Mikhaylovna Moriy (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2016)
The article considers the Soviet historiography of cooperation between the USSR and Germany in the energy sector between the 1960s and 1980s — at a time when two participants of the Cold War put economic interests over political and ideological ones, and embarked on the path of mutually beneficial relations. Based on a fairly wide range of historiographical sources, the authors have identified and analyzed the basic views of Soviet historians on the conditions and terms of the partnership, the nature of implementation of Soviet-Western German energy agreements, the results and effectiveness of cooperation, assessed the impact of energy aspects in the bilateral relations and the international situation as a whole. Special attention is paid to one of the largest compensation agreements signed by the USSR and the Western countries and known as the “deal of the century” — the agreement “Gas for Pipes”. Despite the harsh methodological and ideological framework within which researchers were forced to work during the 1970s — 1980s, the period accumulated a considerable amount of factual material, and interpreted many processes, which to some extent created the basis for a successful development of the topic at the present stage.